2014
DOI: 10.1016/j.molimm.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the HMGB1-derived immunostimulatory peptide Hp91 resides in the helical C-terminal portion and is enhanced by dimerization

Abstract: We have previously shown that an 18 amino acid long peptide, named Hp91, whose sequence corresponds to a region within the endogenous protein HMGB1, activates dendritic cells (DCs) and acts as adjuvant in vivo by potentiating Th1-type antigen-specific immune responses. We analyzed the structure-function relationship of the Hp91 peptide to investigate the amino acids and structure responsible for immune responses. We found that the cysteine at position 16 of Hp91 enabled formation of reversible peptide dimmers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…In addition, antigens presented in a dimeric structure were shown to have enhanced abilities to bind and activate relevant receptors on the surface of immune cells, including B-cells, which could be important for inducing stronger immune responses (Saenz et al, 2014). When analysing dimerization properties of sE and DI/DII proteins, we found that secretory sE (serotypes 3 and 4) were capable of forming stable dimers (approximately 20 % of secreted sE), in agreement with previous reports .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, antigens presented in a dimeric structure were shown to have enhanced abilities to bind and activate relevant receptors on the surface of immune cells, including B-cells, which could be important for inducing stronger immune responses (Saenz et al, 2014). When analysing dimerization properties of sE and DI/DII proteins, we found that secretory sE (serotypes 3 and 4) were capable of forming stable dimers (approximately 20 % of secreted sE), in agreement with previous reports .…”
Section: Discussionsupporting
confidence: 90%
“…They have also been used to deliver CTL vaccine, and the vaccine potency was exaggerated by loading with immunogenic adjuvant, in this case the H 100 peptide, to trigger a desired immune response. The H 100 peptide is specifically suitable in our system because: 1) H 100 is a proven TLR4 agonist and inflammatory mediator [39,40] . 2) It is easily fused at a desired position of the iTEPs and readily produced by a recombinant approach.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion and overlapping analysis of H 91 showed that H91-98, H94-101, or H97-104 did not bind or induce DCs to release IL-6. Only H91-108 (H 91 ) or H100-108 (H 100 ) had the DC stimulatory function, and the effect of H 100 was even stronger than that of H 91 [40] . It is noteworthy that a cysteine (C106 of HMGB1) is present in both H 91 and H 100 but not in the other non-functional HMGB1-derived peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saenz and his group demonstrated that HP91 could function as adjuvant in vivo through potentiating cellular and humoral immune responses [10]. Further studies showed that the region of HP91 which is responsible for its immunostimulatory function is located in the C-terminal, a peptide corresponding to amino acids 100-108 of HMGB1 [10,11]. In this study, we denoted this short peptide as HB 100-108 .…”
Section: Introductionmentioning
confidence: 99%